(untitled) (Proximus Journal of Sports Science and Physical Education, 2025)
The professional training of future physical education teachers requires innovative and effective approaches. Rhythmic gymnastics, with its comprehensive influence on physical, psychological, and pedagogical aspects, serves as a powerful tool in this regard. This article explores the mechanism of increasing professional training through rhythmic gymnastics, emphasizing its role in motor skills development, pedagogical competencies, and overall professional growth